The OEIS is supported by the many generous donors to the OEIS Foundation.

 Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 60th year, we have over 367,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”). Other ways to Give
 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A291820 G.f. A(x,y) satisfies: A( x - x*y*A(x,y), y) = x + x*(1-y)*A(x,y), where the coefficients T(n,k) of x^n*y^k form a triangle read by rows n>=1, for k=0..n-1. 11
 1, 1, 0, 1, 2, 0, 1, 7, 5, 0, 1, 16, 38, 14, 0, 1, 30, 157, 189, 42, 0, 1, 50, 477, 1245, 904, 132, 0, 1, 77, 1197, 5616, 8791, 4242, 429, 0, 1, 112, 2632, 19881, 55566, 57854, 19723, 1430, 0, 1, 156, 5250, 59327, 265204, 491947, 363880, 91366, 4862, 0, 1, 210, 9714, 155783, 1035442, 3062271, 4039551, 2220933, 423124, 16796, 0, 1, 275, 16929, 370205, 3472513, 15217674, 31979723, 31463341, 13285415, 1963169, 58786, 0, 1, 352, 28094, 811877, 10331673, 63678254, 197983540, 310618856, 235959185, 78419541, 9138416, 208012, 0 (list; table; graph; refs; listen; history; text; internal format)
 OFFSET 1,5 COMMENTS More generally, we have the following related identity. Given functions F and G with F(0)=0, F'(0)=1, G(0)=0, G'(0)=0, if F(x - y*G(x)) = x + (1-y)*G(x), then (C1) F(x) = x + G( y*F(x) + (1-y)*x ), (C2) y*F(x) + (1-y)*x = Series_Reversion(x - y*G(x)), (C3) F(x) = x + G(x + y*G(x + y*G(x + y*G(x +...)))), (C4) F(x) = x + Sum_{n>=1} y^(n-1) * d^(n-1)/dx^(n-1) G(x)^n / n!. The g.f. A(x,y) of this sequence equals F(x) in the above when G(x) = x*F(x). LINKS Paul D. Hanna, Table of n, a(n) for n = 1..1035, for rows 1..45 of the triangle in flattened form. FORMULA G.f. A(x,y) also satisfies: (G1) A(x,y) = x + A( y*A(x,y) + x*(1-y), y). (G2) y*A(x,y) + x*(1-y) = Series_Reversion( x - x*y*A(x,y) ). (G3) x*y + (1-y)*B(x,y) = Series_Reversion( x + x*(1-y)*A(x,y) ), where B( A(x,y), y) = x. (G4) A(x,y) = x + Sum_{n>=1} y^(n-1) * d^(n-1)/dx^(n-1) A(x,y)^n * x^n / n!. In formulas 2 and 3, the series reversion is taken with respect to variable x. Formulas for terms: (T1) T(n,0) = 1. (T2) T(n,1) = (n-1)*n*(n+4)/6. for n>=1. (T3) T(n+1,n-1) = binomial(2*n,n)/(n+1) = A000108(n) for n>=1. Row sums: (S1) Sum_{k=0..n-1} T(n,k) = A088714(n-1). (S2) Sum_{k=0..n-1} T(n,k) * 2^(n-k-1) = A276358(n). (S3) Sum_{k=0..n-1} T(n,k) * 3^(n-k-1) = A291744(n). (S4) Sum_{k=0..n-1} T(n,k) * 2^k * 3^(n-k-1) = A291743(n). (S5) Sum_{k=0..n-1} T(n,k) * 2^k = A291813(n). (S6) Sum_{k=0..n-1} T(n,k) * 3^k = A291814(n). (S7) Sum_{k=0..n-1} T(n,k) * 4^k = A291815(n). (S8) Sum_{k=0..n-1} T(n,k) * 3^k * 2^(n-k-1) = A291816(n). (S9) Sum_{k=0..n-1} T(n,k) * 3^k * 4^(n-k-1) = A291817(n). (S10) Sum_{k=0..n-1} T(n,k) * 4^k * 3^(n-k-1) = A291818(n). (S11) Sum_{k=0..n-1} T(n,k) * 4^(n-k-1) = A291819(n). EXAMPLE G.f.: A(x,y) = x + x^2 + (2*y + 1)*x^3 + (5*y^2 + 7*y + 1)*x^4 + (14*y^3 + 38*y^2 + 16*y + 1)*x^5 + (42*y^4 + 189*y^3 + 157*y^2 + 30*y + 1)*x^6 + (132*y^5 + 904*y^4 + 1245*y^3 + 477*y^2 + 50*y + 1)*x^7 + (429*y^6 + 4242*y^5 + 8791*y^4 + 5616*y^3 + 1197*y^2 + 77*y + 1)*x^8 + (1430*y^7 + 19723*y^6 + 57854*y^5 + 55566*y^4 + 19881*y^3 + 2632*y^2 + 112*y + 1)*x^9 + (4862*y^8 + 91366*y^7 + 363880*y^6 + 491947*y^5 + 265204*y^4 + 59327*y^3 + 5250*y^2 + 156*y + 1)*x^10 + (16796*y^9 + 423124*y^8 + 2220933*y^7 + 4039551*y^6 + 3062271*y^5 + 1035442*y^4 + 155783*y^3 + 9714*y^2 + 210*y + 1)*x^11 + (58786*y^10 + 1963169*y^9 + 13285415*y^8 + 31463341*y^7 + 31979723*y^6 + 15217674*y^5 + 3472513*y^4 + 370205*y^3 + 16929*y^2 + 275*y + 1)*x^12 +... such that A( x - x*y*A(x,y), y) = x + x*(1-y)*A(x,y). Also, A(x,y) = x + Z*A(Z, y) where Z = y*A(x,y) + (1-y)*x. ... This triangle of coefficients T(n,k) of x^n*y^k in g.f. A(x,y) begins: 1; 1, 0; 1, 2, 0; 1, 7, 5, 0; 1, 16, 38, 14, 0; 1, 30, 157, 189, 42, 0; 1, 50, 477, 1245, 904, 132, 0; 1, 77, 1197, 5616, 8791, 4242, 429, 0; 1, 112, 2632, 19881, 55566, 57854, 19723, 1430, 0; 1, 156, 5250, 59327, 265204, 491947, 363880, 91366, 4862, 0; 1, 210, 9714, 155783, 1035442, 3062271, 4039551, 2220933, 423124, 16796, 0; 1, 275, 16929, 370205, 3472513, 15217674, 31979723, 31463341, 13285415, 1963169, 58786, 0; 1, 352, 28094, 811877, 10331673, 63678254, 197983540, 310618856, 235959185, 78419541, 9138416, 208012, 0; 1, 442, 44759, 1666522, 27896583, 232505790, 1014785477, 2355151627, 2859824058, 1721756609, 458956233, 42718416, 742900, 0; ... RELATED SEQUENCES. Given T(n,k) is the coefficient of x^n*y^k in g.f. A(x,y), if b(n) = Sum_{k=0..n-1} T(n,k) * p^k * q^(n-k-1) then B(x) = Sum_{n>=1} b(n)*x^n satisfies (E1) B(x - p*x*B(x)) = x + (q-p)*x*B(x) (E2) B(x) = x + Z*B(Z) where Z = p*B(x) + (q-p)*x. ... G.f.s of columns of this triangle begin: C.0: 1/(1-x) C.1: (2 - x)/(1-x)^4 C.2: (5 + 3*x - 4*x^2 + x^3)/(1-x)^7 C.3: (14 + 49*x - 15*x^2 - 9*x^3 + 6*x^4 - x^5)/(1-x)^10 C.4: (42 + 358*x + 315*x^2 - 217*x^3 + 30*x^4 + 18*x^5 - 8*x^6 + x^7)/(1-x)^13 C.5: (132 + 2130*x + 5822*x^2 + 1403*x^3 - 1681*x^4 + 602*x^5 - 50*x^6 - 30*x^7 + 10*x^8 - x^9)/(1-x)^16 C.6: (429 + 11572*x + 62502*x^2 + 82763*x^3 + 2951*x^4 - 9760*x^5 + 5395*x^6 - 1329*x^7 + 75*x^8 + 45*x^9 - 12*x^10 + x^11)/(1-x)^19 C.7: (1430 + 59906*x + 541211*x^2 + 1506161*x^3 + 1217687*x^4 + 16416*x^5 - 35746*x^6 + 36682*x^7 - 13502*x^8 + 2550*x^9 - 105*x^10 - 63*x^11 + 14*x^12 - x^13)/(1-x)^22 C.8: (4862 + 301574*x + 4165915*x^2 + 19578410*x^3 + 34788033*x^4 + 20899306*x^5 + 1681742*x^6 + 174039*x^7 + 195964*x^8 - 103084*x^9 + 28953*x^10 - 4444*x^11 + 140*x^12 + 84*x^13 - 16*x^14 + x^15)/(1-x)^25 ... Thus A(x, y*(1-x)^3)*(1-x) = x + 2*y*x^3 + (5*y^2 - y)*x^4 + (14*y^3 + 3*y^2)*x^5 + (42*y^4 + 49*y^3 - 4*y^2)*x^6 + (132*y^5 + 358*y^4 - 15*y^3 + y^2)*x^7 +... MATHEMATICA nmax = 13; A[x_] = x; Do[A[x_] = x + (y A[x] + (1-y) x) A[y A[x] + (1-y) x] + x O[x]^n // Normal // Expand // Collect[#, x]&, {n, nmax}]; T[n_, k_] := SeriesCoefficient[A[x], {x, 0, n}, {y, 0, k}]; Table[T[n, k], {n, 1, nmax}, {k, 0, n-1}] // Flatten (* Jean-François Alcover, Oct 20 2019 *) PROG (PARI) {T(n, k) = my(A=x); for(i=1, n, A = x + subst(x*A, x, y*A + (1-y)*x +x*O(x^n)) ); polcoeff(polcoeff(A, n, x), k, y)} for(n=1, 12, for(k=0, n-1, print1(T(n, k), ", ")); print("")) CROSSREFS Cf. A088714 (row sums), A291821 (central terms), A291822 (diagonal). Cf. A291813, A291814, A291815, A291816, A291817, A291818, A291819. Cf. A276358, A291743, A291744. Cf. A277295 (variant). Sequence in context: A325754 A154974 A342981 * A309124 A078341 A199459 Adjacent sequences: A291817 A291818 A291819 * A291821 A291822 A291823 KEYWORD nonn,tabl AUTHOR Paul D. Hanna, Sep 01 2017 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified December 9 18:33 EST 2023. Contains 367693 sequences. (Running on oeis4.)